(untitled) (Milli Mála, 2015)
This article deals with two nautical loanwords in Spanish which appear to be of Nordic or Scandinavian origin and borrowed via French. The history of the words is traced, their journey from one language to another examined and their adoption and assimilation to the system of the recipient language discussed. The first written sources of the nautical loanwords of Nordic origin in Spanish are old texts, mainly navigation books, dictionaries of nautical terms and chronicles dating from the sixteenth and seventeenth centuries and onwards. These nautical words were incorporated into French in the twelfth and thirteenth centuries and entered other Romance languages from the thirteenth until the seventeenth centuries through French; some entered later. The words discussed here are guindaste, ‘windlass’, and guindar, ‘to wind’, and their derivations.